Panenteisme Dalam Pemikiran Barat dan Islam - Suhermanto Ja’far (Ulumuna, 2010)
Among themes in the studies about God is about problem of existential relationship between God, humans, and nature. The problem has spawned various perspectives, either normative-theological or metaphysical-ontological. Panentheism which is included in the second perspective is a concept that emphasizes the divinity of all in God, not all is God as in the view of pantheism. This paper aims to examine the concept of panentheism by comparing its views developed in the West with those in Islam. West panentheism, as developed by Whitehead, views God as an infinite conceptual reality of absolute possibilities. His existence is not a creation, but He exists with all creations. While in Islamic panentheism, as stated by Iqbal, human pantheistic experience with God does not vanish human ego, but human ego even will be more authentic and powerful as it is in the Lord. He rejects pantheism view that all is God.